ISOLASI DAN KARAKTERISASI SENYAWA FLAVONOID DARI KULIT AKAR TUMBUHAN SUKUN Artocarpus altilis (Parkinson) Fosberg - Prio Santoso (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2018)
Isolation of flavonoid compounds from Plants Roots Leather Breadfruit (Artocarpus altilis (Parkinson) Fosberg) that grow in the village of Banjar District State Tanggamus Wonosobo regency of Lampung Province has been conducted. Isolation of flavonoid compounds is done by maceration method using the solvent ethyl acetate. Stages of purification of samples carried out by chromatographic methods include vacuum liquid chromatography (VLC), thin layer chromatography (TLC), gravity column chromatography (GCC), and flash chromatography. As for the characterization of flavonoid compounds used infrared spectroscopy (IR), ultaviolet-visible spectroscopy (UV-Vis), nuclear magnetic resonance spectroscopy (NMR), and test the melting point. Based on theÂ resultsÂ of research that has been done, pure flavonoid compounds obtained amorphous form of yellow crystals with a melting point of 247,5-249 0C. Based on the analysis of ultraviolet-visibleÂ spectroscopy, infrared, and nuclear magnetic resonance can be concluded that the isolation of these compounds is artonin E.